Effects of Irrigation Scheduling on Yield of Potato and Water Productivity Southern, Ethiopia - Kedrala Wabela; Tagese Bekele; Mohammed Ahmed (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Irrigation water is one of the major limiting factors that affect crop production in Ethiopia. Irrigation scheduling is an important technique for quantifying water required by plants at a particular interval to improve irrigation efficiency. The objective of this study was to evaluate the irrigation scheduling effects on potato yield and water productivity. The study was designed in four experimental treatments as: 5, 7, 9 days intervals, and Farmer practice arranged in randomized complete block design with three replications. The two years combined yield results showed that a maximum yield of 21.99ton/ha was obtained from 9 days irrigation interval treatment and a minimum yield of 15.80ton/ha was obtained from Farmer’s practice. Maximum and minimum water productivity of 3.34 kg/m3 and 2.4 kg/m3 were obtained from 9-day irrigation intervals and farmers’ practice, respectively. From these results, it can be observed that to attain the maximum potato yield and water productivity in the study area, it is better to use 9-days irrigation interval with a determined irrigation water amount.